Котлован: повести, роман / Андрей Платонов - Платонов Андрей Платонович (Удмуртия, 1989)
Экземпляры: ф. 2 (20100914) / Инвентарный номер: 96177 / Цена: 15.00 / Авт.знак: П 37 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6